Infant mortality and social causality: Lessons from the history of Britain’s public health movement, c. 1834–1914 - Nosrati, E; Kelly, MP; Szreter, S (Wiley, 2024)
What are the historical conditions under which a sociologically informed understanding of health inequality can emerge in the public sphere? We seek to address this question through the lens of a strategically chosen historical puzzle—the stubborn persistence of and salient variation in high infant mortality rates across British industrial towns at the dawn of the previous century—as analysed by Arthur Newsholme, the Medical Officer of the Local Government Board. In doing so, we retrace the historical processes through which the evolving public health movement gradually helped crystallise a scientific understanding of the social causes of excess mortality. We map the dominant ideology of the public sphere at the time, chart the shifting roles of the state, and retrace the historical origins and emergence of ‘public health’ as a distinctive category of state policy and public discourse. We situate the public health movement in this historical configuration and identify the cracks in the existing ideological and administrative edifice through which this movement was able to articulate a novel approach to population health—one that spotlights the political economy of social inequality. We relate this historical sequence to the rise of industrial capitalism, the social fractures that it spawned, and the organised counter‐movements that it necessitated.